Assessing Police Attitudes Toward Intervention in Gender Violence: the Role of Training, Perceived Severity, and Myths About Intimate Partner Violence Against Women - Serrano-Montilla, Celia; Garrido-Macías, Marta; Sáez-Díaz, Javier; Sáez, Gemma (Journal of family violence, 2025)
Purpose Even though evidence has broadly confirmed that public attitudes toward intervention shape the decision-making process when dealing with IPVAW events, rather less is known about what determines the police decision-making process. Research support that police attitudes toward intervention in IPVAW explain differences when police officers response to IPVAW events. This research analyzes the combined role of IPVAW myths, perceived severity, and IPVAW training in reactive (tolerance for IPVAW and minimal police involvement) and proactive (important police task and pro-arrest) police attitudes toward intervention in gender violence. Methods Drawing from snowball sampling, we collected responses of 211 Spanish police officers via online subject-recruitment platform. Results The main findings of our study confirmed that IPVAW myths lead to less proactive attitudes toward intervention both directly and through a reduction in the perceived severity of IPVAW. Importantly, we found a moderating role of IPVAW training, suggesting that the endorsement of IPVAW myths leads to less proactive responses, but only for untrained police officers. Conclusions Our findings suggest the importance of IPVAW training on police proactive attitudes toward intervention via IPVAW myths instead of perceived severity. Police training programs to both novice and experienced officers should be focused on confronting IPVAW myths in order to improve police perception, evaluation and involvement in gender violence events.